Municipal environment and conservation standards in Colombia: ¿protected areas, ecological networks or green infrastructures? (2011)
General conservation-related land use standards comprise environmentally important areas according to the principles of preservation, restoration and sustainable usage, which internationally consist of three categories, all conceptually different from each other depending on their particular components: i) protected areas, ii) ecological networks, and iii) green infrastructures. The articleanalyzes those general conservation standards in 32 Colombian municipalities in order to determine to which they respond for the most part, methodologically, by studying all local Territorial Planning Documents to establish which conservation standards were used, how they named, defined and classified them, and which components were considered, taking the name of the standard implemented in each town literally from the Plans studied. Then, each conservation standard found was classified as a protected area, an ecological network or a green infrastructure, based on the components accounted for and their classification. As a result, fifty general conservation standards were found under twenty-eight different denominations, mostly correspondent to ecological networks, followed by green infrastructures and, in a smaller amount, a combination of those two. It was also observed that, although structured by a great variety of environmental elements, as a common feature, all standards included water system components.